Exotic and not-so-exotic candidates for ultrahigh energy cosmic rays - Swain, John (2001)
Ultrahigh energy cosmic rays present a major unsolved puzzle. Not only do we not know their origin, but we also have no really solid evidence that they are protons or iron nuclei—the two most popular candidates. We examine briefly a couple of “nonstandard” possibilities: light magnetic monopoles, which are rather exotic, and nuclei heavier than iron, which are perhaps less exotic, but have many attractive features.